Efektivitas Penanganan dan Pengelolaan Sampah Rumah Tangga Berkonsep 3R di Kelurahan Cempaka Putih Barat - Novan Syahbani; Hendra Wijayanto; Angella Rosha Pangestu (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Population growth, changes in consumption patterns, and people's lifestyles have increased the amount of waste generation, type, and diversity of waste characteristics. Increasing the volume of waste that requires management. Waste management that is not used will have a negative impact on health and will also greatly disrupt environmental sustainability, be it residential areas, rivers and seas. The type and method of research used is descriptive research, which can be interpreted as a process of solving problems related to the method of describing or describing the condition of the subject and object of research at this time based on the facts that appear or how they are. While the method used is a qualitative research method to describe the actual conditions in detail and in detail in view of the actual cases and research objectives. This study aims to determine the effectiveness of handling and managing waste with the 3R concept in the Cempaka Putih Barat Village area. The amount of data used lies in the Cempaka Putih Barat Village area, data collection through observation and documentation in analyzing data obtained directly from the field. The results of this study indicate that the 3R policy program (reuse, reduce, recycle) made by the Environmental Service for handling and managing household waste is running well in the Cempaka Putih Barat Village area, this is because the amount of waste generated is less than in the Cempaka Village area. Putih Tengah, so that it can be interpreted that the effectiveness of handling and managing household waste has a positive impact on the environment and increases the income of the surrounding community.